The Multifaceted Contributions of Community-Based Breeding Program of Bonga Sheep to Flock Dynamics, Animal Performance, and Socio-economic Benefits of Beneficiaries in Kafa Zone, Ethiopia - Metsafe Mamiru; Aberra Melesse; Aynalem Haile; Tesfaye Getachew (Advances in Agriculture)
The community-based breeding program (CBBP) for Bonga sheep was introduced with the objective of improving the productivity of sheep and income of producers. Technical evaluation of the program reported outstanding outcomes in growth and reproductive traits of the animals. Further participatory evaluation allowing farmers to assess the relevance and impact of such programs has been suggested. This paper thus aims to explore the multifaceted contributions of the CBBP of Bonga sheep, emphasizing its flock dynamics, improvements in animal performance, and socio-economic benefits as perceived by beneficiaries. Data were generated through interviews of 222 (111 CBBP members and 111 nonmembers) randomly selected sheep producers. The survey focused on flock dynamics, improvement in biological and aesthetic traits, and livelihood change of farmers. Logistic regression, ANOVA, and Pearson’s chi-square were the analysis methods used. Results revealed that CBBP members had better flock size by 42.6% and they had higher numbers of breeding rams, suckling lambs, and breeding ewes in their flock by 60.5%, 54.3%, and 41.6%, respectively, compared to non-members. The study further showed that members acquired and lost more (<0.001) animals annually than non-members. About 94.6%, 82.8%, and 81.1% of respondents witnessed the improvement in body size, twinning rate, and survival of lambs, respectively. Likewise, 97.3% of members reported substantial improvement in reproductive traits such as age at first lambing (92.8%) and lambing interval (93.7%). Improvement in aesthetic traits like tail size (92.8%) and coat color (92%) too was reported by the farmers. The CBBP farmers produced, slaughtered, and sold more animals than their non-CBBP counterparts. They also acquired more income by 60%, which enabled them to store assets and fulfill routine home needs better than non-members. In conclusion, CBBP positively influenced sheep assets, performance, and marketability, elevating the income and livelihoods of beneficiaries. This underlines the need for expansion of the program to benefit more farmers.